Multiple Organ Dysfunction After Cardiosurgical Interventions - L. S. Barbarash; Ye. V. Grigoryev; G. P. Plotnikov; B. L, Hayes; G. V. Moiseyenkov; D. L. Shukevich; S. V. Ivanov; Yu. N. Odarenko (Общая реаниматология)
Objective: to study the clinical efficiency of introducing an algorithm for organ-protective intensive care. Materials and methods. 3278 case histories of patients admitted to the clinic in 2000—2009 for surgical treatment (under extracorporeal circulation) for coronary heart disease (CHD) and acquired heart defects (AHD) were retrospectively analyzed. Throughout the analyzed period, the patients operated on for CHD and AHD were 2068 (63.1%) and 1210 (36.9%), respectively; the postoperative incidence of multiple organ dysfunction (MOD) among all the patients was 11.8% (378 patients); mortality in MOD was 3.75% (n=123) of the operated patients (included into the study) or 32.5% of all the patients with MOD. Conclusion. The incidence of MOD is in proportion to the number of surgical interventions and depends on their specific features (recurrence, baseline severity, comorbidity, or multifocal atherosclerosis). Preventive intensive therapy for MOD reduced mortality and altered its syndromic pattern towards a preponderance of pyoseptic complications. Key words: cardiosurgery, extracorporeal circulation, multiple organ dysfunction.